Liquid biopsy of fine-needle aspiration supernatant for lung cancer genotyping. (August 2018) - Guibert, Nicolas; Tsukada, Hisashi; Hwang, David H.; Chambers, Emily; Cibas, Edmund S.; Bale, Tejus; Supplee, Julianna; Ulrich, Bryan; Sholl, Lynette M.; Paweletz, Cloud P.; Oxnard, Geoffrey R.
Highlights: FNA supernatant, usually discarded, is a rich source of cell-free DNA. Driver and resistance mutations were detected by NGS and ddPCR in supernatant. This widely available biospecimen may increase paucicellular FNA yield. Supernatant cfDNA has potential for facilitating rapid cancer genotyping. Abstract: Background: Tumor genotyping is transforming lung cancer care but requires adequate tumor tissue. Advances in minimally invasive biopsy techniques have increased access to difficult-to-access lesions, but often result in smaller samples. With the advent of highly sensitive DNA genotyping methods used for plasma analysis, we hypothesized that these same methods might allow genotyping of free DNA derived from fine needle aspiration supernatant (FNA-S). Methods: We studied patients with known or suspected lung cancer undergoing fine needle aspirate (FNA). After spinning the sample for cellblock, the FNA-S (usually discarded) was saved for genotyping. Supernatant cell-free DNA (SN-cfDNA) was extracted and tested by both droplet digital PCR ( EGFR, BRAF, KRAS mutations) and highly sensitive amplicon-based next-generation sequencing (NGS). Results: 17 samples were studied, including 11 FNAs from patients with suspected lung cancer and 6 FNAs from patients with lung cancer and acquired drug resistance. Of 6 newly diagnosed adenocarcinomas, 4 had a driver mutations (1 EGFR, 2 KRAS, 1 HER2 ) found on tissue; all of these could be detected in SN-cfDNA. The EGFR driver mutation was detected in all 5 adenocarcinomas with acquired EGFR resistance and the EGFR T790 M in three cases, in agreement with cellblock. Conclusions: FNA-S is a rich source of fresh tumor DNA, potentially increasing the diagnostic yield from small FNAs. Through use of emerging techniques for highly sensitive genotyping, this widely available biospecimen has potential for facilitating rapid cancer genotyping at diagnosis and after drug resistance.